Current Bioinformatics Tools in Precision Oncology - Tesfaye Wolde; Vipul Bhardwaj; Vijay Pandey (MedComm)
ABSTRACT Integrating bioinformatics tools has profoundly transformed precision oncology by identifying essential molecular targets for personalized treatment. The rapid development of high‐throughput sequencing and multiomics technologies creates complex datasets that require robust computational methods to extract meaningful insights. Nonetheless, the clinical application of multiomics data continues to pose significant challenges. This review explores advanced bioinformatics tools utilized within multiomics, emphasizing their pivotal role in discovering cancer biomarkers. Cloud‐based platforms, such as Galaxy and DNAnexus, facilitate streamlined data processing, while single‐cell analysis software, including Seurat, identifies rare cellular subpopulations. Further integration of artificial intelligence with machine learning approaches improves predictive modeling and diagnostic accuracy. Spatial omics technologies correlate molecular signatures within tumor microenvironments, guiding treatment strategies. Bioinformatics integrates these technologies to establish a new standard in precision oncology, thereby enhancing therapy efficacy. Collaborative initiatives between The Cancer Genome Atlas and cBioPortal expedite advancements through the sharing open data and implementing standardized methodologies. Advancing multiomics integration techniques alongside improved computational capabilities is essential for discovering new biomarkers and refining precision medicine strategies. Future efforts should focus on merging multiomics techniques with innovative computational methods to drive novel biomarker discovery and improve precision medicine applications.